Bundled Payments in Otolaryngology: Early Lessons from Arkansas. (December 2018) - Rathi, Vinay K.; Metson, Ralph; Varvares, Mark A.; Naunheim, Matthew R.; Gray, Stacey T.
The Medicare Access and CHIP Reauthorization Act (MACRA) of 2015 established value-based reimbursement as the new norm in health care. As part of this shift, public and private insurers have adopted bundled payments in an effort to improve quality and control cost. Arkansas recently implemented an otolaryngology-specific bundled payment, which reimburses episodes of care involving adenoidectomy and/or tonsillectomy. In this mandatory model, otolaryngologists have the potential for shared savings or losses based on spending relative to risk-adjusted historical benchmarks and performance on quality metrics. The initiative has resulted in reduced health care costs and rates of postoperative antibiotic prescription and secondary bleeding. However, this experiment also illustrates potential pitfalls with bundled payments, such as emphasis of quality metrics lacking clinical relevance and incentive for increased service volume. The Arkansas initiative offers important lessons for otolaryngologists as ongoing reform under MACRA brings episode-based care to the forefront of our field.